The Effect of ALMA, Equity, and Liabilities on Financial Performance and Company Value of Indonesian Banks - Natasya, Rizky; Ramadani, Zahira Naswa; Safana, Alya; Hidayah, Siti Nur; Aliah, Nur (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study was designed to identify the influence of Asset and Liability Management (ALMA), equity, and liabilities on financial performance and the value of banking companies in Indonesia. ALMA is a crucial strategy for maintaining bank financial stability through balanced asset and liability management. Meanwhile, equity and liabilities reflect the capital structure, which underpins a bank's ability to absorb risk and sustainably operate.This study utilizes an explanatory quantitative method that empirically explains the relationships between variables.The data for this study were obtained from the financial statements of the banks selected as the sample. The research findings demonstrate that ALMA and equity positively influence financial performance, while liabilities negatively influence it. Furthermore, financial performance has been shown to play a significant role in increasing company value. These findings indicate that effective asset and liability management, along with a strong capital structure, can generate positive performance and enhance investor perceptions of bank company value. This study is expected to contribute to broadening financial management insights and serve as a reference for the banking industry in developing more effective financial management strategies.